ISOLASI ACTINOMYCETES DARI TANAH KEBUN SEBAGAI BAHAN PETUNJUK PRAKTIKUM MIKROBIOLOGI - Pujiati Pujiati (UNIVERSITAS PGRI MADIUN, 2014)
The objective of this study was to isolate actinomycetes from soil of tea plantations, Jamus ngawi as a microbiology lab manual chapter isolation and characterization of microbes. The medium used is the medium of MHA and MHB. Soil samples taken to a depth of 10-15 cm from the surface with capture location is about 07o 41'53,07 'S and 111o 37' 24.64 '' E. The isolates were obtained observed morphologic characters include colony shape, colony color, surface characteristics of colonies, colony growth, colony elevation, and the edge of the colony. Isolates of actinomycetes were successfully isolated are Streptomyces, Nocardia and Nocardiopsis. Actinomycetes isolates have been found that can be used as a collection of the microbiology laboratory.